Policy uncertainty and the demand for money in Japan - Mohsen Bahmani-Oskooee; Majid Maki Nayeri (Review of Economic Analysis (REA), 2020)
In an attempt to establish stability of the demand for money, some recent studies have included the volatility of the money supply and output to account for uncertainty. In this paper we consider the experience of Japan but rather than including an uncertainty measure related to money supply and output, we include a relatively more comprehensive measure known as Economic Policy Uncertainty. When we included this lat er measure, we were unable to find a stable money demand in Japan. However, when we introduced the nonlinear adjustment of policy uncertainty, we not only found a stable money demand but also meaningful estimates. Since the approach allows us to assess asymmetries, we found that in Japan the public hold more cash when there is an increase or a decrease in uncertainty.
Keywords: E41; 330; Money Demand; Japan; Policy Uncertainty; Asymmetry; Nonlinear ARDL